A reduced modified lignin-based activated carbon for supercapacitor electrode material and preparation method and application thereof

The reduction-modified lignin-based activated carbon was prepared by carbonization followed by activation, which solved the problem of unsatisfactory energy storage effect of lignin-based supercapacitor materials in the existing technology. It also achieved electrode materials with high specific surface area and porous structure, thus improving electrochemical performance and industrial applicability.

CN117334487BActive Publication Date: 2026-11-06FUJIAN AGRI & FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210726892.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-24
Publication Date
2026-11-06
Estimated Expiration
2042-06-24

AI Technical Summary

Technical Problem

Existing lignin-based supercapacitor materials have unsatisfactory energy storage performance, and the low yield is caused by the direct reaction between the activator and lignin in the preparation process.

Method used

A carbonization-activated carbon method was adopted, in which alkali lignin was mixed with an excess reducing agent, the pH was adjusted, and then carbonized and activated to prepare reduction-modified lignin-based activated carbon, thereby increasing its specific surface area and porous structure and enhancing its electrochemical performance.

Benefits of technology

It significantly improves the specific surface area and pore volume of reduction-modified lignin-based activated carbon, enhances its electrochemical performance, and exhibits excellent electrochemical cycle stability and high specific capacitance, making it suitable for the industrial production of supercapacitor electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117334487B_ABST
    Figure CN117334487B_ABST
Patent Text Reader

Abstract

This invention belongs to the technical field of capacitor electrode materials, and discloses a reduction-modified lignin-based activated carbon for supercapacitor electrode materials, its preparation method, and its application. The preparation method of the reduction-modified lignin-based activated carbon provided by this invention includes the following steps: mixing and reacting an excess reducing agent with black liquor containing alkali lignin, or an alkaline solution containing lignin, followed by adjusting the pH to 1-7 with an inorganic acid to precipitate alkali lignin, filtering, washing, and drying to obtain reduced lignin; and then subjecting the reduced lignin to carbonization and activation reactions under an inert atmosphere to obtain reduction-modified lignin-based activated carbon. The activated carbon obtained by this preparation method uses reduced-modified lignin as raw material, the carbonization process does not involve the addition of toxic chemical reagents, and the activation reaction can use commonly used activators such as potassium hydroxide or sodium hydroxide to obtain a high-performance activated carbon material for supercapacitors, realizing the high-value utilization of alkali lignin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of capacitor electrode material technology, specifically relating to a reduction-modified lignin-based activated carbon for supercapacitor electrode materials, its preparation method, and its application. Background Technology

[0002] With the widespread adoption of portable electronic devices and increasingly serious environmental problems, the demand for new, efficient, smaller, and more flexible energy storage devices has surged. Next-generation energy storage systems not only need to meet the requirements of sustainable development but also require higher power density, longer cycle life, and a more environmentally friendly operating environment. Porous carbon is a widely applicable and highly promising electrode material. Its relatively low cost, ease of fabrication, and environmental friendliness make it suitable for supercapacitor applications.

[0003] Currently, carbon precursors under research include biomass, coal-based materials, and petroleum. Among them, biomass waste has attracted much attention due to its advantages such as renewability, environmental friendliness, and wide availability. Lignin, a biomass waste, is a major component of waste liquid in the pulp and paper industry and industrial residue in the fuel ethanol industry, with less than 2% being effectively utilized. How to achieve high-value-added comprehensive utilization of lignin to improve the economic efficiency of pulp and paper and fuel ethanol production is becoming a hot topic of research. Because lignin has a large number of benzene ring structures in its molecular chain and a carbon content of over 50%, it has a high yield and is considered an ideal precursor for carbon materials.

[0004] Currently, many researchers have conducted in-depth studies on lignin-based carbon supercapacitors, but their energy storage effect is far from ideal.

[0005] Existing technology discloses a method for preparing graphene / lignin-based activated carbon, including: 1) preparing lignin-based activated carbon; 2) mixing graphene oxide and activated carbon to obtain a graphene oxide / lignin-based activated carbon composite; 3) activating the composite with an alkali, followed by high-temperature pyrolysis and reduction to obtain a graphene / lignin-based activated carbon composite material; and 4) preparing an electrode sheet. In step 1), lignin and an alkaline substance are dissolved in deionized water, stirred, evaporated to dryness, and then pyrolyzed at high temperature under an inert atmosphere to obtain lignin-based activated carbon; the alkaline substance is sodium hydroxide or potassium hydroxide, or a mixture of sodium hydroxide and potassium hydroxide. The mass ratio of lignin to the alkaline substance in step 1) is 1:1 to 1:6, and the high-temperature pyrolysis temperature and time are 500-900℃ and 1-4 hours, respectively. The supercapacitor prepared by this technology can achieve a discharge capacity of over 90 F / g at 20 A / g. The obtained graphene / lignin-based activated carbon composite material exhibits an electrical conductivity exceeding 25 S / cm under a pressure of 20 MPa. When used as an electrode material for supercapacitors, it achieves a specific capacitance of 130 Fg. -1After 1000 charge-discharge cycles, its capacity can still be maintained at over 96%.

[0006] Existing technology discloses a conjugated lignin for supercapacitor electrodes and its preparation method. The method involves using acylation or esterification reagents as reactants to protect the phenolic hydroxyl groups of lignin under acidic conditions. Subsequently, the lignin with protected phenolic hydroxyl groups is crosslinked with a conjugated crosslinking agent in an organic acid solvent to obtain a lignin with a conjugated structure. The resulting conjugated lignin is then used as a cathode material in supercapacitors, enabling the capacitors to exhibit high energy storage performance and high power density. The obtained succinyl-cross-conjugated lignin was tested in a half-cell experiment in a 0.5 M H₂SO₄ electrolyte solution at a current density of 1 A·g⁻¹. -1 At that time, its specific capacitance was 367.707 A·h·g. -1 When the current density is 2A·g -1 At that time, its specific capacitance was 253.33 A·h·g. -1 Its energy density is 7.97 W·h·kg. -1 The power density is 150.05 × 10³ W·kg. -1 When the current density is 5 A·g -1 At that time, its specific capacitance was 213.95 A·h·g -1 Its energy density is 6.70 W·h·kg. -1 The power density is 376.84 × 10³ W·kg -1 Furthermore, a half-cell was assembled using the prepared succinyl cross-conjugated lignin as a stainless steel anode material, achieving an energy density of 11.43 W·h·kg⁻¹. -1 The power density is 76.18 × 10³ W·kg -1 .

[0007] Existing technology discloses a porous carbon material for alkali lignin-based supercapacitors, its preparation method, and its application. The method involves mixing crudely purified alkali lignin from papermaking black liquor with a triblock polymer, Pluronic F127, and Mg(CH3COO)2·4H2O. Formaldehyde and hydrochloric acid are then added and thoroughly stirred to obtain a homogeneous mixture. This mixture is dried in an oven to obtain a dark brown solid. The dark brown solid is then placed in a tube furnace for carbonization. After the reaction, nitrogen or inert gas is continuously introduced to cool it to room temperature. Finally, the mixture is acid-washed, water-washed, and dried to obtain a black powdery porous carbon material. The obtained porous carbon material is thoroughly ground to a particle size of less than 10 μm. Electrode materials are prepared according to a mass ratio of porous carbon material: acetylene black: PTFE = 85%: 10%: 5%. The electrochemical performance is measured using a three-electrode system with 1 mol / L H2SO4 as the electrolyte. This porous carbon material has a BET specific surface area as high as 679.4 m².2 / g, total pore volume is 0.83cm³ 3 / g. At a current density of 1A / g, the specific capacitance can reach 101.4F / g. Summary of the Invention

[0008] To address the problems of the prior art, the present invention provides a reduction-modified lignin-based activated carbon for use in supercapacitor electrode materials; Another object of the present invention is to provide a method for preparing reduction-modified lignin-based activated carbon for use as electrode material in supercapacitors; Another object of the present invention is to provide a conductive ink containing the reduced-modified lignin-based activated carbon used as a supercapacitor electrode material.

[0009] Another object of the present invention is to provide an application of reduction-modified lignin-based activated carbon for use in supercapacitor electrode materials.

[0010] The objective of this invention is achieved through the following technical solution: A reduction-modified lignin-based activated carbon for use as an electrode material in supercapacitors, in the form of a black powder, has a specific surface area of ​​1600.7~2328.59 m². 2 ·g -1 The total pore volume is 0.85~1.21cm. 3 ·g -1 The pore sizes are mainly micropores and mesopores, with micropores having a specific surface area of ​​1450.7~1992.92 m². 2 ·g -1 The micropore volume is 0.7~0.98 cm³. 3 ·g -1 The mesoporous specific surface area is 59.3~99.3 m². 2 ·g -1 The mesopore volume is 0.12~0.25cm³. 3 ·g -1 The bulk density is 0.56~0.85cm³. 3 ·g -1 The particle size distribution ranges from 200 nm to 2000 nm. Infrared spectroscopy shows that the reduced-modified lignin-based activated carbon, compared to unmodified lignin-based activated carbon, exhibits higher particle size distribution at 1730 cm⁻¹. -1 The C=O stretching vibration peak is more obvious.

[0011] Preferably, the specific surface area of ​​the reduction-modified lignin-based activated carbon is 2328.59 m². 2 ·g -1 The total pore volume is 1.21 cm³. 3 ·g -1The pore sizes are mainly micropores and mesopores, with the micropores having a specific surface area of ​​1992.92 m². 2 ·g -1 The micropore volume is 0.954 cm³. 3 ·g -1 The mesoporous specific surface area is 99.3 m². 2 ·g -1 The mesopore volume is 0.25 cm³. 3 ·g -1 The bulk density is 0.83 cm³. 3 ·g -1 The particle size distribution is 200nm~2000nm.

[0012] The reduced-modified lignin-based activated carbon of the present invention has two advantages. First, the reduced lignin, after carbonization and activation, possesses a large specific surface area and a porous structure. Since mesopores can be used for ion transport and diffusion, and micropores can be used to enhance charge storage, the porous structure is beneficial for energy storage in double-layer capacitors. Second, the oxygen-containing functional groups not only improve the hydrophilicity / wetting properties of the material and reduce the contact resistance at the interface between the carbon material and the electrolyte, but also provide many electrochemical active sites, contributing to pseudocapacitance by participating in the redox reactions on the electrode material surface.

[0013] A method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials includes the following steps: Step 1: Mix an excess of reducing agent with pulping black liquor containing alkali lignin or an alkaline solution containing lignin and react thoroughly. After reacting at 30-60℃ for 8-12 hours, adjust the pH to 1-7 with an inorganic acid to precipitate alkali lignin. Filter, wash, and dry to obtain reduced lignin. Step 2: The reduced lignin from Step 1 is carbonized under an inert atmosphere. After continuously passing inert gas and cooling to room temperature, it is washed and dried with water, inorganic acid and organic solvent to obtain primary lignin char. Step 3: Mix primary lignin charcoal with KOH and / or NaOH activators evenly, and carry out the activation reaction under an inert atmosphere. After continuously introducing inert gas and naturally cooling, wash and dry with water, inorganic acid and organic solvent to obtain reduced modified lignin-based activated carbon.

[0014] This invention innovatively employs a pre-carbonization followed by activation method, which significantly improves the yield from biomass source to final activated carbon compared to a one-step activation method, increasing the yield from 10% to 36%. In the one-step activation method, lignin reacts directly with the activator (alkali) to generate small molecule monomers that volatilize, resulting in a lower yield.

[0015] Preferably, the pulping black liquor containing alkali lignin is wastewater generated in the alkaline pulping process of the papermaking industry.

[0016] More preferably, the pulping black liquor containing alkali lignin is wastewater generated in the sulfate pulping process.

[0017] Preferably, the alkaline solution containing lignin is a sodium hydroxide solution or a potassium hydroxide solution containing lignin.

[0018] More preferably, the alkaline solution containing lignin is a sodium hydroxide solution.

[0019] Preferably, the reducing agent is one or more of dithionite, sulfurous acid, formamidinium sulfinic acid, sodium borohydride, and potassium borohydride.

[0020] More preferably, the reducing agent is sodium borohydride.

[0021] Preferably, in step 1, the inorganic acid is either hydrochloric acid or sulfuric acid, with a concentration of 0.5~10 mol / L.

[0022] More preferably, in step 1, the inorganic acid is 6 mol / L hydrochloric acid.

[0023] Preferably, the molecular weight of the reduced lignin is 1500-5000. Infrared spectroscopy shows that, compared to virgin lignin, reduced lignin has more methoxy groups, more hydroxyl groups, and fewer carbonyl groups.

[0024] Specifically, the reduction treatment imparts more hydroxyl groups to lignin, which increases the proportion of COC in the carbon structure after carbonization and activation. This increases the accessibility of the electrolyte to the carbon material, thereby improving its electrochemical performance.

[0025] Preferably, in step 2, the carbonization reaction specifically involves reducing lignin to 500-700°C at a heating rate of 1-30°C / min and holding it at that temperature for 1-2 hours.

[0026] More preferably, in step 2, the carbonization reaction specifically involves reducing lignin to 600°C at a heating rate of 5°C / min and holding it at that temperature for 1.5 hours.

[0027] Preferably, in step 3, the activation reaction specifically involves mixing primary lignin charcoal and activator at a mass ratio of 1:(3~6) until uniform, and then heating to 600~800 ℃ at a heating rate of 1~30℃ / min under an inert atmosphere and holding at that temperature for 1~3h.

[0028] More preferably, in step 3, the activation reaction specifically involves: mixing primary lignin charcoal and activator at a mass ratio of 1:4, heating to 650 °C at a heating rate of 5 °C / min under a nitrogen atmosphere, and then holding at that temperature for 2 hours.

[0029] A conductive ink containing the reduced-modified lignin-based activated carbon used as a supercapacitor electrode material is prepared by mixing the reduced-modified lignin-based activated carbon, conductive carbon black, and a binder.

[0030] Preferably, the mass ratio of the reduced modified lignin-based activated carbon, the conductive carbon black, and the binder is (7~8):(1~2):(0.5~1).

[0031] More preferably, the mass ratio of the reduced modified lignin-based activated carbon, the conductive carbon black, and the binder is 8:1:1, 7:2:1, or 8:1.5:0.5.

[0032] Preferably, the adhesive is either polytetrafluoroethylene or polyvinylidene fluoride.

[0033] Application of a reduction-modified lignin-based activated carbon containing the aforementioned electrode material for supercapacitors in the preparation of supercapacitors.

[0034] Compared with the prior art, the beneficial effects of the technical solution of the present invention are: 1. The reduction-modified lignin-based activated carbon prepared by this invention has a large specific surface area, reaching a maximum of 2328.59 m². 2 ·g -1 The material exhibits well-developed ultrapores smaller than 1 nm, as well as micropores of 1-2 nm and mesopores of 2-3 nm, with a maximum total pore volume of 1.21 cm³. 3 ·g -1 The bulk density of the reduction-modified lignin-based activated carbon prepared by this invention is 0.83 cm³. 3 ·g -1 The bulk density of unmodified lignin-based activated carbon is 0.55 cm³. 3 ·g -1 The bulk density of the original lignin-based activated carbon is increased by 32%.

[0035] 2. The reduction-modified lignin-based activated carbon prepared in this invention has simple process conditions. This material exhibits excellent electrochemical performance, characterized by stable electrochemical cycling and high specific capacitance. At a current density of 0.5 A / g in a 1 mol / L sulfuric acid electrolyte, its specific capacitance is 638.25 F·g. -1 This is far higher than the specific capacitance of existing commercial activated carbon. More importantly, even when expanded by 20 times (10 A·g), it still achieves a higher specific capacitance. -1 At high scan rates, the specific capacitance remains at 350.75 F·g. -1 (at 0.5A·g) -1At its initial capacitance of 54.96%, it exhibits excellent rate performance. Compared with traditional double-layer supercapacitor electrodes, reduction-modified lignin-based activated carbon has superior electrochemical performance, and the electrode material preparation process is simple, making it suitable for large-scale production in enterprises. Attached Figure Description

[0036] Figure 1 The image shows the Fourier Transform Infrared (FTIR) spectra of virgin lignin (KL) and reduced lignin (RKL) in Example 1 of this invention. Figure 2 (a) X-ray photoelectron spectroscopy (XPS) of lignin char (C-KL) in Comparative Example 1 and primary lignin char (C-RKL) in Comparative Example 3 of the present invention; Figure 2 (b) X-ray photoelectron spectroscopy (XPS) spectra of lignin activated carbon (CA-KL) in Comparative Example 2 and reduction-modified lignin-based activated carbon (CA-RKL) in Example 1 of the present invention; Figure 3 (a) The lignin-based activated carbon modified by reduction at different carbonization temperatures in Examples 1-3 of the present invention at a current density of 0.5 A g. -1 The constant current charge-discharge curve (GCD) plot at time t, Figure 3 (b) is a cyclic voltammetry (CV) curve of the reduction-modified lignin-based activated carbon at different carbonization temperatures in Examples 1-3 of the present invention, at a scan rate of 10 mV / s. Figure 3 (c) is a graph showing the rate performance test curves of reduction-modified lignin-based activated carbon at different carbonization temperatures in Examples 1-3 of this invention. Figure 3 (d) is the electrochemical impedance (EIS) fitting curve of the reduction-modified lignin-based activated carbon at different carbonization temperatures in Examples 1-3 of the present invention (equivalent circuit diagram and partial enlarged view are used as internal insets). Figure 4 (a) The lignin-based activated carbon modified by reduction at different activation temperatures in Examples 1 and 4-6 of the present invention, at a current density of 0.5 A g. -1 The constant current charge-discharge curve (GCD) plot at time t, Figure 4 (b) is a cyclic voltammetry (CV) curve of the reduction-modified lignin-based activated carbon at different activation temperatures in Examples 1 and 4-6 of the present invention, at a scan rate of 10 mV / s. Figure 4 (c) is a rate performance test curve of reduction-modified lignin-based activated carbon at different activation temperatures in Examples 1 and 4-6 of the present invention. Figure 4 (d) is the electrochemical impedance (EIS) fitting curve of the reduction-modified lignin-based activated carbon at different activation temperatures in Examples 1 and 4-6 of the present invention (equivalent circuit diagram and partial enlarged view are used as internal insets). Figure 5 (a) The lignin-based activated carbon modified by reduction under different amounts of activator in Examples 1 and 7-9 of the present invention at a current density of 0.5 A g. -1 The constant current charge-discharge curve (GCD) plot at time t, Figure 5 (b) is a rate performance test curve of the reduction-modified lignin-based activated carbon under different amounts of activator in Examples 1 and 7-9 of the present invention. Figure 5 (c) is a cyclic voltammetry (CV) curve of the lignin-based activated carbon modified by reduction under different amounts of activator in Examples 1 and 7-9 of the present invention, with a scan rate of 10 mV / s. Figure 5 (d) is the electrochemical impedance (EIS) fitting curve of the reduced modified lignin-based activated carbon under different amounts of activator in Examples 1 and 7-9 of the present invention (equivalent circuit diagram and partial enlarged view are used as internal insets). Figure 6 (a) The reduction-modified lignin-based activated carbon (CA-RKL) and lignin activated carbon (CA-KL) in Example 1 and Comparative Example 2 of the present invention were tested at a current density of 0.5 A g. -1 The constant current charge-discharge curve (GCD) plot at time t, Figure 6 (b) is a cyclic voltammetry (CV) curve of the reduction-modified lignin-based activated carbon (CA-RKL) and lignin activated carbon (CA-KL) in Example 1 and Comparative Example 2 of the present invention at a scan rate of 10 mV / s. Figure 6 (c) is the electrochemical impedance (EIS) fitting curve of reduction modified lignin-based activated carbon (CA-RKL) and lignin activated carbon (CA-KL) in Example 1 and Comparative Example 2 of the present invention (equivalent circuit diagram and local magnification diagram are used as internal inset). Figure 6 (d) and Figure 6 (e) are cyclic voltammetry (CV) curves of the reduction-modified lignin-based activated carbon (CA-RKL) and lignin activated carbon (CA-KL) at different scan rates in Example 1 and Comparative Example 2 of the present invention, respectively. Figure 6 (f) is a graph showing the rate performance test curves of reduction-modified lignin-based activated carbon (CA-RKL) and lignin activated carbon (CA-KL) in Example 1 and Comparative Example 2 of the present invention. Figure 7 The nitrogen adsorption and desorption isotherms and corresponding DFT pore size distribution curves of the reduction-modified lignin-based activated carbon (CA-RKL), lignin carbon (C-KL), lignin activated carbon (CA-KL), and primary lignin carbon (C-RKL) in Example 1 and Comparative Examples 1-3 of this invention are shown. Figure 8The X-ray diffraction (XRD) patterns of the reduction-modified lignin-based activated carbon (CA-RKL), lignin carbon (C-KL), lignin activated carbon (CA-KL), and primary lignin carbon (C-RKL) in Example 1 and Comparative Examples 1-3 of this invention are shown. Figure 9 The images show the Raman spectra of the reduction-modified lignin-based activated carbon (CA-RKL), lignin carbon (C-KL), lignin activated carbon (CA-KL), and primary lignin carbon (C-RKL) in Example 1 and Comparative Examples 1-3 of this invention. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of this application will be clearly and completely described below with reference to the accompanying drawings of the embodiments of this application. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the described embodiments without creative effort are within the scope of protection of this application.

[0038] Unless otherwise specified, the reagents, methods and equipment used in this invention are conventional reagents, methods and equipment in this technical field.

[0039] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.

[0040] Example 1 Step 1: Take 200 ml of pulping black liquor and place it in a beaker. Add 5 g of sodium borohydride powder, seal the beaker, and sonicate it for 30 min. Then, place it in a 60 ℃ constant temperature water bath for 8 h. After the reaction, adjust the pH of the solution to 2 with 6 mol / L hydrochloric acid to precipitate alkali lignin (lignin in this invention is abbreviated as KL). Filter the lignin and wash it twice with deionized water. Finally, dry it in a vacuum drying oven to obtain reduced lignin (RKL).

[0041] Step 2: Place 10g of reduced lignin (RKL) in a tube furnace and heat it to the target temperature of 600℃ at a rate of 5℃ / min under a nitrogen atmosphere, holding it at that temperature for 1 h. The gas flow rate is 200 mL / min. After cooling to room temperature, wash the obtained black powder successively with 1 mol / L hydrochloric acid, deionized water, and ethanol until pH = 7, and dry it at 105℃ for 4 h to obtain primary lignin char (C-RKL).

[0042] Step 3: Primary lignin-based activated carbon (C-RKL) and KOH are mixed evenly at a mass ratio of 1:4. The mixture is placed in a tube furnace and heated to the target temperature of 650 ℃ at a rate of 5 ℃ / min under a nitrogen atmosphere, and held at this temperature for 2 h. The gas flow rate is 200 mL / min. After cooling to room temperature, the obtained black solid powder is washed successively with 2 mol / L hydrochloric acid, deionized water, and ethanol until pH = 7, and then dried in an oven at 100 ℃ for 4 h to obtain reduced-modified lignin-based activated carbon (CA-RKL).

[0043] Conductive ink is obtained by mixing reduced modified lignin-based activated carbon (CA-RKL) particles, conductive carbon black, polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF) in a weight ratio of 8:1:1 and grinding them thoroughly for 60 min until they are uniformly mixed.

[0044] Examples 2-11 The preparation steps of the reduction-modified lignin-based activated carbon in Examples 2-11 are the same as those in Example 1, except for the following process conditions, as shown in Tables 1.1 and 1.2.

[0045] Table 1.1

[0046] Table 1.2

[0047] Comparative Example 1 In this comparative example, unmodified lignin (KL) was used to prepare lignin charcoal (C-KL). The preparation method only included step 2 of Example 1, and the process conditions were the same as in Example 1. The final lignin charcoal (C-KL) was characterized and analyzed. The specific preparation method is as follows: 10 g of lignin (KL) was placed in a tube furnace and heated to the target temperature of 600 °C at a rate of 5 °C / min under a nitrogen atmosphere and held for 1 h. The gas flow rate was 200 mL / min. After cooling to room temperature, the obtained black powder was washed successively with 1 mol / L hydrochloric acid, deionized water, and ethanol until pH = 7, and then dried at 105 °C for 4 h to obtain unmodified lignin char (C-KL).

[0048] Unmodified lignin carbon (C-KL) particles, conductive carbon black, polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 8:1:1 and ground thoroughly for 60 minutes to obtain a uniformly mixed conductive ink.

[0049] Comparative Example 2 In this comparative example, unmodified lignin (KL) was used to prepare lignin activated carbon (CA-KL). The preparation method only included steps 2 and 3 of Example 1, and the process conditions were the same as in Example 1. The final lignin activated carbon (CA-KL) was characterized and analyzed. The specific preparation method is as follows: 10 g of lignin (KL) was placed in a tube furnace and heated to the target temperature of 600 °C at a rate of 5 °C / min under a nitrogen atmosphere and held for 1 h. The gas flow rate was 200 mL / min. After cooling to room temperature, the obtained black powder was washed successively with 1 mol / L hydrochloric acid, deionized water, and ethanol until pH = 7, and then dried at 105 °C for 4 h to obtain unmodified lignin char (C-KL).

[0050] Unmodified lignin activated carbon (C-KL) was mixed with KOH at a mass ratio of 1:4 and placed in a tube furnace. The mixture was heated to the target temperature of 650 °C at a rate of 5 °C / min under a nitrogen atmosphere and held for 2 h at a gas flow rate of 200 mL / min. After cooling to room temperature, the resulting black solid powder was washed successively with 2 mol / L hydrochloric acid, deionized water, and ethanol until pH = 7, and then dried in an oven at 100 °C for 4 h to obtain lignin activated carbon (CA-KL).

[0051] The conductive ink is obtained by mixing lignin activated carbon (CA-KL) particles, conductive carbon black, polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF) in a weight ratio of 8:1:1 and grinding them thoroughly for 60 minutes.

[0052] Comparative Example 3 The preparation method of this comparative example only includes steps 1 and 2 of Example 1, and the process conditions are the same as in Example 1. The final primary lignin charcoal (C-RKL) was characterized and analyzed. The specific preparation method is as follows: Take 200 ml of pulping black liquor and place it in a beaker. Add 5 g of sodium borohydride powder, seal the beaker, and sonicate it for 30 min. Then, place it in a 60 ℃ constant temperature water bath for 8 h. After the reaction, adjust the pH of the solution to 2 with 6 mol / L hydrochloric acid to precipitate alkali lignin (lignin in this invention is abbreviated as KL). Filter the lignin and wash it twice with deionized water. Finally, dry it in a vacuum drying oven to obtain reduced lignin (RKL).

[0053] 10 g of reduced lignin (RKL) was placed in a tube furnace and heated to the target temperature of 600 °C at a rate of 5 °C / min under a nitrogen atmosphere, and held at that temperature for 1 h. The gas flow rate was 200 mL / min. After cooling to room temperature, the obtained black powder was washed successively with 1 mol / L hydrochloric acid, deionized water, and ethanol until pH = 7, and then dried at 105 °C for 4 h to obtain primary lignin char (C-RKL).

[0054] Primary lignin charcoal (C-RKL) particles, conductive carbon black, polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 8:1:1 and then ground thoroughly for 60 minutes to obtain a uniformly mixed conductive ink.

[0055] The conductive materials prepared according to the various embodiments and comparative examples of the present invention were analyzed and tested, as follows: 1. Analytical Methods (1) Fourier transform infrared spectroscopy (FTIR) analysis The FT-IR spectra of the samples were tested using a Bruker VERTEX 70 microscope (Germany): The samples were thoroughly dried in a drying oven (120 °C, 12 h). Spectroscopic-grade potassium bromide was mixed with the sample at a mass ratio of 100:1, ground evenly, compressed into a pellet, and then tested. The spectral range was 400–4000 cm⁻¹. -1 The resolution is set to 1 cm. -1 .

[0056] (2) X-ray photoelectron spectroscopy (XPS) analysis The sample was scanned across the entire spectrum using a Thermo ESCALAB 250 X-ray photoelectron spectrometer, with a focus on the energy signals of elements such as C, O, S, and N.

[0057] (3) Electrochemical performance testing The electrochemical performance of lignin-based activated carbon was characterized using a three-electrode system. The electrolyte was 1 mol·L⁻¹. -1 H₂SO₄ electrolyte. A saturated calomel electrode (SCE) was used as the reference electrode, a platinum sheet as the counter electrode, and the sample as the working electrode. The voltage window for testing was set to 0–0.8 V (vs. SCE). When assembling the materials into a symmetrical supercapacitor device, 1 mol·L⁻¹... - 1 When H2SO4 is used as the electrolyte, the voltage window is 0-1.0V; when an ionic liquid (EMIMBF4) is used as the electrolyte, the voltage window is 0-3.5V. The separator used in the symmetrical supercapacitor is a polypropylene membrane, which is placed between two circular carbon electrodes of the same mass (active material) and size to form a simple sandwich structure device.

[0058] 1) Cyclic voltammetry (CV). CV was performed using a CHI 760E electrochemical workstation at a scan rate of 10 mV / s.

[0059] 2) Galvanostatic charge-discharge (GCD) testing was conducted on the LAND CT3002A Blue Battery testing system, using a current density of 0.5-10 A·g. -1 .

[0060] 3) Electrochemical Impedance Spectroscopy (EIS) test: In this paper, the electrochemical impedance spectrum of the supercapacitor was tested and obtained under open circuit voltage using a CHI 760E electrochemical workstation. The voltage amplitude used was 5 mV and the frequency ranged from 0.01 Hz to 100,000 Hz.

[0061] 4) Cyclic stability testing of materials in supercapacitors: This paper uses the LAND CT200 2A battery testing system to test the cyclic stability of materials under constant current density.

[0062] (4) Specific surface area and pore structure (BET) analysis The samples were subjected to dry nitrogen isothermal adsorption analysis using a micropore analyzer (ASAP 2020) at 77 K (liquid nitrogen bath). The surface area, pore diameter, and pore volume of the samples were calculated using the Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) analytical theories.

[0063] (5) Bulk density analysis Take a sample, and mix the conductive agent (carbon black) and binder (PTFE) in a mass ratio of 8:1:1 until homogeneous. Add an appropriate amount of ethanol as a dispersant, mix and grind in an agate mortar, then drop the mixture into an infrared mold and dry it in a vacuum drying oven at 50 degrees Celsius. Press the mixture into tablets using an infrared tablet press (769YP-30T) with a force of 10 MPa. Measure the length, width, and height of the pressed carbon tablets using a micrometer; the volume is length * width * height. Accurately weigh the tablets, and the resulting bulk density is mass divided by volume.

[0064] (6) X-ray diffraction (XRD) analysis XRD analysis was performed on the samples using an X-ray powder diffractometer (ESCALAB 250, Thermo Fisher Scientific, Germany) to investigate their chemical composition, crystal structure, graphitization process, and carbon structural density. The scanning range was 5–60°, and the scanning speed was 10° / min. -1 .

[0065] (7) Raman spectroscopy analysis The Raman spectroscopy of the sample was performed using a DXR 532 Raman spectrometer to determine the degree of graphitization. The laser wavelength was set to 532 nm.

[0066] 2. Analysis Results (1) Fourier transform infrared spectroscopy (FTIR) analysis results First, infrared spectral analysis was performed on the RKL prepared in step 1 of Examples 1-9 and the original KL, and the molecular weight of the reduced lignin was measured to be 1500-5000. Figure 1 As shown, 1325 cm -1 The absorption of lilac kernels at the lignin site showed no significant change, indicating that this reaction had little effect on the benzene ring structure of lignin. (KL lignin at 1715 cm⁻¹) -1 Represents the C=O stretching vibration of the non-conjugated benzene ring, 1677 cm⁻¹ -1 Representing the stretching of the C=O conjugated with the benzene ring, after reduction, RKL's 1715 cm⁻¹ -1 With 1677 cm -1 The absorption peaks all showed varying degrees of attenuation, while the 1370 cm⁻¹ peak showed a decrease. -1 The enhanced stretching vibration of the aromatic nucleus in the RKL indicates an increase in phenolic hydroxyl groups on the benzene ring. This suggests that sodium borohydride can reduce conjugated carbonyl groups to hydroxyl groups, and can also reduce some non-conjugated carbonyl groups to hydroxyl groups.

[0067] (2) X-ray photoelectron spectroscopy (XPS) analysis results Secondly, XPS spectra analysis was performed on the conductive materials prepared in Examples 1 and Comparative Examples 1-3. The final products prepared in Examples 1 and Comparative Examples 1-3 were named CA-RKL, C-KL, CA-KL, and C-RKL, respectively. The XPS O1s spectra analysis results of the conductive materials prepared in Examples 1 and Comparative Examples 1-3 are as follows: Figure 2 As shown. Figure 2As shown in (a), C-RKL contains 4.89% chemisorbed oxygen, while C-KL contains 5.81% chemisorbed oxygen. This indicates that C-RKL has more available oxygen than C-KL. C-RKL contains 16.5% C=O, 33.62% COC, 27.75% C-OH, 8.33% COOR, 3.31% quinone groups, and 10.41% chemisorbed oxygen. Studies have shown that, compared to phenolic hydroxyl groups, quinones, and carbonyl groups, COOR (carboxylic acids, lactones, and anhydrides) are thermally unstable and decompose at lower temperatures. Therefore, after activation with KOH at 650 °C, a large amount of COOR preferentially decomposes to form CO2 and H2O. KOH reacts with C at higher temperatures to etch and create pores, and molten KOH preferentially reacts with C on COC to form C-OH. Furthermore, hydroxyl groups transform to C=O at high temperatures and further decompose to form CO. Simultaneously, some hydroxyl groups also form in-plane COC, further polymerizing the lignin carbon. These processes occur simultaneously, and KOH preferentially reacts with C to etch rather than with OH radicals. In summary, the degree of deoxygenation during lignin carbon activation is far greater than that of oxygenation, resulting in a significant decrease in the final oxygen content of the activated carbon. Therefore, CA-RKL contains a large number of C=O, C-OH, and quinone oxygen-containing groups. In acidic electrolyte media, since each quinone group has two electrons participating in a redox reaction, the capacitance of the quinone group is higher than that of other groups. On the other hand, the stability of hydroxyl groups (C-OH) and quinone groups (C=O) on the carbon surface is better than that of carboxyl groups (COOH). Therefore, the high content of C=O and C-OH on the carbon surface can improve its hydrophilicity and electrochemical pseudocapacitive properties.

[0068] Furthermore, oxygen-containing functional groups on the surface of micropores / mesoporous materials contribute more to pseudocapacitance than those in carbon materials, while in-plane COC structures facilitate mesopore formation, improve electrolyte accessibility to functional groups, and thus enhance pseudocapacitive performance.

[0069] (3) Electrochemical performance test results 1) Electrochemical analysis was performed on the conductive materials prepared in Examples 1-3. Table 1.1 shows that after obtaining reduced lignin in step 1, the carbonization temperatures in steps 2-3 of Examples 1-3 were 600℃, 500℃, and 700℃, respectively, with other process conditions remaining the same. The electrochemical test results of the conductive materials prepared in Examples 1-3 are as follows: Figure 3 As shown. The samples prepared in Examples 1 to 3 were named C-Temperature 600 ℃, C-Temperature 500 ℃, and C-Temperature 700 ℃.

[0070] Figure 3 (a) is a current density of 0.5 A g -1The constant current charge-discharge curves (GCD) at 600℃ showed the longest discharge time, exhibiting the best capacitance performance. All GCD curves were isosceles triangles with some distortion during discharge, indicating that pseudocapacitance, in addition to the electric double layer pairs, also contributed to the improved capacitance. This is because lignin modification allows the oxygen functional groups in the carbon material to provide more pseudocapacitance and more active sites.

[0071] Figure 3 (b) shows the cyclic voltammetry (CV) curves of the conductive material. The rectangular area is largest at a C-Temperature of 600 °C. However, the CV curve is not strictly rectangular and exhibits a significant reversible redox peak around 0.3 V, indicating that pseudocapacitance contributes to the capacitance improvement in addition to the double-layer pairs. The specific capacitance of all samples decreases with increasing current. This is because as the current increases, electrolyte ions do not have enough time to diffuse fully into the micropores, and the pseudocapacitance does not have enough time to undergo redox reactions, leading to a decrease in charge accumulation and thus a reduction in capacitance. Based on the formula for calculating the specific capacitance of the three electrodes, the specific capacitance of the electrodes at C-Temperature 500 °C, C-Temperature 600 °C, and C-Temperature 700 °C is approximately 0.5 A·g. -1 The calculated values ​​are 540.18 F·g. -1 638.75F·g -1 and 538.52 F·g -1 The C-Temperature at 600 °C exhibits the best electrochemical performance.

[0072] Figure 3 (c) shows the rate performance test curve of the conductive material. The curve shows that, under the carbonization temperature condition of C-Temperature 600 ℃, even with a 20-fold increase (10 A·g)... -1 At high scan rates, the specific capacitance remains at 350.75 F·g. -1 (at 0.5A·g) -1 At that time, it was 54.96% of its initial capacitance, demonstrating excellent rate performance.

[0073] Figure 3(d) shows the electrochemical impedance spectroscopy (EIS) fitting curves of the conductive material (equivalent circuit diagram and local magnification diagram are used as internal insets). The EIS was fitted to establish an equivalent circuit model. Table 2 gives the detailed values ​​of each circuit element. In the high-frequency region, the intercept of the semicircle with the X-axis represents the internal resistance Rs of the electrode. In the mid-frequency region, the diameter of the semicircle represents the charge transfer resistance Rct of the electrode. In the low-frequency region, it has a certain offset from the Y-axis. This is because the capacitance of the carbon electrode in each curve comes not only from the double-layer capacitance but also from the pseudocapacitance. W is the resistance of the constant-phase element. From the magnified diagram of the high-frequency region, it can be seen that the equivalent series resistance (Rs) of the C-Temperature 500 ℃, C-Temperature 600 ℃, and C-Temperature 700 ℃ electrodes are 1.024 Ω, 0.811 Ω, and 1.060 Ω, respectively. Among them, the C-Temperature 600 ℃ electrode has the lowest internal resistance and the highest conductivity. The electrochemical performance of CA-RKL first increases and then decreases with increasing carbonization temperature, and the electrochemical performance is optimal when the carbonization temperature is 600℃.

[0074] Table 2

[0075] 2) Electrochemical analysis was performed on the conductive materials prepared in Examples 1 and 4-6. Table 1.1 shows that after obtaining reduced lignin in step 1 in Examples 1 and 4-6, the activation temperatures in step 3 were 650℃, 600℃, 700℃, and 800℃, respectively, with other process conditions remaining the same. The electrochemical test results of the conductive materials prepared in Examples 1 and 4-6 are as follows: Figure 4 As shown. The samples prepared in Examples 1, 4 to 6 were named CA-Temperature 650 ℃, CA-Temperature 600 ℃, CA-Temperature 700 ℃ and CA-Temperature 800 ℃.

[0076] Figure 4 (a) is for a current density of 0.5 A·g -1 The constant current charge-discharge curves (GCD) at 650 °C showed the longest discharge time, exhibiting the best capacitance performance. All GCD curves were isosceles triangles with some distortion during discharge, indicating that pseudocapacitance, in addition to the electric double layer pairs, also contributed to the improved capacitance. This is because lignin modification allows the oxygen functional groups in the carbon material to provide more pseudocapacitance and more active sites.

[0077] Figure 4(b) shows the cyclic voltammetry (CV) curves of the conductive material. The rectangular area is largest at CA-Temperature 650 ℃. However, the CV curve is not strictly rectangular and exhibits a significant reversible redox peak around 0.3 V, indicating that pseudocapacitance contributes to the capacitance improvement in addition to the double-layer pairs. The specific capacitance of all samples decreases with increasing current. This is because as the current increases, electrolyte ions do not have enough time to diffuse fully into the micropores, and the pseudocapacitance does not have enough time to undergo redox reactions, leading to a decrease in charge accumulation and thus a reduction in capacitance. Based on the formula for calculating the specific capacitance of the three electrodes, the specific capacitance of the electrodes at CA-Temperature 600 ℃, CA-Temperature 650 ℃, CA-Temperature 700 ℃, and CA-Temperature 800 ℃ is around 0.5 A·g. -1 The calculated values ​​are 478.75 F·g. -1 638.25 F·g -1 490.58.75 F·g -1 360.96 F·g -1 CA-Temperature 650 ℃ exhibits the best electrochemical performance.

[0078] Figure 4 (c) is the rate performance test curve of the conductive material. The curve shows that at CA-Temperature 650 °C, even with a 20-fold increase (10 A·g)... -1 At high scan rates, the specific capacitance remains at 350.75 F·g. -1 (at 0.5A·g) -1 At that time, it was 54.96% of its initial capacitance, demonstrating excellent rate performance.

[0079] Figure 4 (d) is the fitting curve of the electrochemical impedance (EIS) of the conductive material (equivalent circuit diagram is the same). Figure 3(c) The local magnification plot is used as an internal inset. An equivalent circuit model was established by fitting the EIS. Table 3 shows the detailed values ​​of each circuit element. Similar to the test results above, the magnified high-frequency region plot shows that the equivalent series resistances (Rs) of the CA-Temperature 600 ℃, CA-Temperature 650 ℃, CA-Temperature 700 ℃, and CA-Temperature 800 ℃ electrodes are 0.931 Ω, 0.811 Ω, 0.868 Ω, and 1.618 Ω, respectively. Among them, the CA-Temperature 650 ℃ electrode has the lowest internal resistance and the highest conductivity. The electrochemical performance of CA-RKL shows a trend of first increasing and then decreasing with increasing activation temperature, reaching its optimal performance at an activation temperature of 650 ℃.

[0080] Table 3

[0081] 3) Electrochemical analysis was performed on the conductive materials prepared in Examples 1 and 7-9. Table 1.2 shows that in Examples 1 and 7-9, after obtaining reduced lignin in step 1, the mass ratios of primary lignin char and activator in step 3 were 1:4, 1:3, 1:5, and 1:6, respectively, with other process conditions remaining the same. The electrochemical test results of the conductive materials prepared in Examples 1 and 7-9 are as follows: Figure 5 As shown. The samples obtained in Examples 1, 7-9 were named C:KOH=1:4, C:KOH=1:3, C:KOH=1:5 and C:KOH=1:6.

[0082] Figure 5 (a) is a current density of 0.5 A g -1 The constant current charge-discharge curves (GCD) at different times showed that the discharge time was longest and the capacitance performance was best when C:KOH = 1:4. All GCD curves were isosceles triangles with some distortion during discharge, indicating that pseudocapacitance, in addition to the electric double layer pairs, also contributed to the improvement of capacitance. This is because lignin modification allows the oxygen functional groups of the carbon material to provide more pseudocapacitance and more active sites.

[0083] Figure 5(c) shows the cyclic voltammetry (CV) curves of the conductive material. The rectangular area is largest when C:KOH = 1:4. However, the CV curve is not strictly rectangular and exhibits a significant reversible redox peak around 0.3 V, indicating that pseudocapacitance contributes to the capacitance improvement in addition to the double-layer pairs. The specific capacitance of all samples decreases with increasing current. This is because as the current increases, electrolyte ions do not have enough time to diffuse fully into the micropores, and the pseudocapacitance does not have enough time to undergo redox reactions, leading to a decrease in charge accumulation and thus a reduction in capacitance. Based on the formula for calculating the specific capacitance of the three-electrode, the specific capacitance of the C:KOH = 1:4 electrode is approximately 0.5 A·g. -1 The calculated value is 638.25 F·g. -1 The specific capacitance is much higher than that of C:KOH=1:3, C:KOH=1:5, and C:KOH=1:6. C:KOH=1:4 shows the best electrochemical performance.

[0084] Figure 5 (b) is the rate performance test curve of the conductive material. The curve shows that at C:KOH=1:4, even when the rate is increased by 20 times (10 A·g), the conductivity remains high. -1 At high scan rates, the specific capacitance remains at 350.75 F·g. -1 (at 0.5A·g) -1 At that time, it was 54.96% of its initial capacitance, demonstrating excellent rate performance.

[0085] Figure 5 (d) is the fitting curve of the electrochemical impedance (EIS) of the conductive material (equivalent circuit diagram is the same). Figure 3 (c) The local magnification diagram is used as an internal inset. The equivalent circuit model was established by fitting the EIS. Table 4 gives the detailed values ​​of each circuit element. Similarly, from the magnified diagram of the high-frequency region, it can be seen that the equivalent series resistances Rs of C:KOH=1:3, C:KOH=1:4, C:KOH=1:5, and C:KOH=1:6 are 1.209 Ω, 0.811 Ω, 1.397 Ω, and 2.249 Ω, respectively. The lowest internal resistance of C:KOH=1:4 indicates that the conductivity of this material is the highest and the electrochemical performance of this electrode is the best.

[0086] Table 4

[0087] 4) Electrochemical analysis was performed on the conductive materials prepared in Example 1 and Comparative Example 2. Comparative Example 2 used unmodified lignin (KL) to prepare lignin activated carbon (CA-KL), and its preparation method only included steps 2 and 3 of Example 1, with the process conditions being the same as in Example 1. The electrochemical test results of the conductive materials prepared in Example 1 and Comparative Example 2 are as follows: Figure 6 As shown. The samples prepared in Example 1 and Comparative Example 2 were named CA-RKL and CA-KL, respectively.

[0088] Figure 6 (a) is for a current density of 0.5 A·g -1 The constant current charge-discharge curves (GCD) at different current densities are shown. The curves are approximately isosceles triangles with obvious redox peaks. CA-KL and CA-RKL curves are shown at a current density of 0.5 A·g⁻¹. -1 The specific capacitance at that time was 363.54 F·g. -1 and 638.25 F·g -1 As the current density increases, the specific capacitance begins to decrease. This is because, with increasing current, electrolyte ions do not have enough time to fully diffuse into the micropores, and the pseudocapacitance does not have enough time to undergo redox reactions, resulting in a decrease in charge accumulation and thus a decrease in capacitance. The GCD curves show that the discharge time, in descending order, is CA-RKL > CA-KL. The electrochemical performance reflects the quality of the material's pore structure and the degree of O doping effect.

[0089] Figure 6 (b) shows the cyclic voltammetry (CV) curves of CA-RKL and CA-KL. As can be seen from the figure, the rectangular area enclosed by CA-RKL is significantly larger than that of CA-KL. In comparison, CA-RKL has excellent electrochemical performance.

[0090] Figure 6 (d) and (e) show the CV curves of CA-RKL and CA-KL at different scan rates (10-100 mV / s). The curves show that both have excellent capacitance characteristics.

[0091] Figure 6 (c) Electrochemical impedance (EIS) fitting curves for CA-RKL and CA-KL (equivalent circuit diagram is the same). Figure 3 (c) The local magnification diagram is used as an internal inset. Its EIS was fitted to establish an equivalent circuit model. Table 5 gives the detailed values ​​of each circuit element. Similarly, from the magnified diagram of the high-frequency region, it can be seen that the equivalent series resistance Rs of CA-RKL and CA-KL are 0.811Ω and 1.568Ω, respectively. The lowest internal resistance of CA-RKL indicates that the conductivity of this material is the highest. The electrode made of CA-RKL has the best electrochemical performance.

[0092] Figure 6 (f) shows the rate performance test curves for CA-RKL and CA-KL. The curves show that even when CA-RKL is scaled up by 20 times (10 A·g), the performance remains the same. -1 It also demonstrates excellent rate performance.

[0093] Table 5

[0094] (4) Specific surface area and pore structure (BET) analysis results Pore ​​size analysis was performed on the conductive materials prepared in Examples 1-9 and Comparative Examples 1-3, and the results are shown in Tables 6.1 and 6.2. As can be seen from Tables 6.1 and 6.2, the specific surface area of ​​the reduced-modified lignin-based activated carbon produced in this invention is 1600.7~2328.59 m². 2 / g, total pore volume is 0.85~1.21cm³ 3 ·g -1 The specific surface area of ​​the micropores is 1450.7~1992.92 m². 2 / g, micropore volume is 0.7~0.98cm³ 3 ·g -1 The mesoporous specific surface area is 59.3~99.3 m². 2 / g, mesoporous pore volume is 0.12~0.25cm³ 3 ·g -1 . Figure 7 These are the nitrogen adsorption and desorption isotherms and corresponding DFT pore size distribution curves of the conductive materials obtained in Example 1 and Comparative Examples 1-3. Figure 7 (a) It can be seen that the adsorption-desorption curves of both CA-RKL and CA-KL carbon material samples are type I linear (according to IUPAC classification), and there is no hysteresis loop. When the relative pressure is less than 0.01, the adsorption capacity of CA-RKL and CA-KL increases rapidly and quickly reaches saturation, indicating the presence of a large number of micropores and ultramicropores. Figure 7 (b) It can be seen that the pore size at all levels of the carbon material was enhanced after KOH activation. Compared with the CA-KL sample, CA-RKL has more pores larger than 1.7 nm, and the pores of 2-2.5 nm are more developed, and the mesopores are larger than 0.11 nm. 3 g -1 It becomes 0.25 m 3 g -1 .

[0095] As shown in Table 6.2, comparing Example 1 and Comparative Example 3, the specific surface area (Sa) of the layered porous carbon after KOH treatment was significantly higher. BETThe total pore volume (Vt) and micropore volume (Vmi) increased significantly, for example, C-RKL, with the specific surface area increasing from 199.53 cm². 3 ·g -1 Increased to (CA-RKL) 2328.59 m 2 ·g -1 The total pore volume is 0.12 cm³. 3 ·g -1 Increased to 1.21 m 3 ·g -1 The micropore volume ranges from 0.078 cm³. 3 ·g -1 Increased to 0.954 m 3 ·g -1 The volume of the mesopores ranges from 0.038 cm³. 3 ·g -1 Increased to 0.25cm 3 ·g -1 This indicates that the KOH activation process generates additional micropores and widens some of these micropores to form mesopores. This conclusion is consistent with... Figure 7 (b) The pore size distribution is consistent. Studies have shown that the formation of mesopores can promote ion migration to the interface, which in turn improves the utilization of micropores. In summary, lignin after carbonization and reactivation, CA-KL and CA-RKL have reasonable pore structures: since mesopores can be used for ion transport and diffusion, and micropores can be used to enhance charge storage, the porous structure is beneficial for the energy storage of double-layer capacitors. It can be seen that CA-RKL has better electrochemical performance because it has a larger specific surface area and more mesopores than CA-KL.

[0096] Table 6.1

[0097] Table 6.2

[0098] (5) Bulk density analysis results The bulk density of the conductive materials prepared in Examples 1-9 and Comparative Examples 1-3 was analyzed, and the results are shown in Tables 7.1 and 7.2. As can be seen from Tables 7.1 and 7.2, the bulk density of the reduction-modified lignin-based activated carbon generated in Examples 1-9 of this invention ranges from 0.56 to 0.85 cm³. 3 ·g -1 Between. As shown in Table 7.2, the bulk density of the unreduced CA-KL sample in Comparative Example 2 is 0.55 cm³. 3 ·g -1 The bulk density of the CA-RKL sample in Example 1 after reduction was 0.83 cm³. 3·g -1 This indicates that the porosity between lignin activated carbon particles is reduced after reduction. Combined with the above analysis of pore structure (BET), it can be seen that the reduction of lignin results in an increase in the number of micropores and mesopores in the activated carbon particles, leading to a decrease in porosity and an increase in bulk density.

[0099] Table 7.1

[0100] Table 7.2

[0101] (6) X-ray diffraction (XRD) analysis results XRD analysis was performed on the conductive materials prepared in Example 1 and Comparative Examples 1-3. Figure 8 It can be seen that lignin completes the carbonization process through high-temperature pyrolysis carbonization, that is, under the heat treatment condition of 600 ℃, lignin realizes the transformation into carbon material through thermal decomposition. Two broad diffraction peaks are shown near 24° and 43°, corresponding to the (002) crystal plane and (100) crystal plane, respectively, indicating that C-KL and C-RKL have the characteristic peaks of amorphous carbon. After pore formation with KOH at 650 ℃, the (002) peak of the samples (CA-KL, CA-RKL) shows a slight weakening and broadening compared with the carbonized samples (C-KL, C-RKL). This indicates that the crystallinity of the samples is weakened, there are more defects, and the number of nanopores increases, resulting in a discontinuous carbon matrix structure.

[0102] (7) Raman spectroscopy analysis results Raman spectroscopy analysis was performed on the conductive materials prepared in Example 1 and Comparative Examples 1-3. As is well known, the D peak represents the irregular vibrational structure and material defects of porous carbon materials, and the G peak represents the sp of hexagonal crystals. 2 Vibration peaks are generally expressed using the integral intensity ratio (I). D / I G As a method for evaluating the degree of graphite order in carbon materials, I D / I G The larger the ratio, the more disordered the graphite structure. Figure 9 It can be seen that the I of the carbonized samples (CA-KL, CA-RKL) D / I G The ratios were 0.80 and 0.83, respectively. The activated samples (CA-KL and CA-RKL) I... D / I G The ratios gradually increased to 1.24 and 1.02, respectively. Compared with their respective carbonized samples, the activated samples had more defects and a greater degree of cross-sectional disorder. It was the presence of defects that increased the specific capacitance.

[0103] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A reduction-modified lignin-based activated carbon for use as an electrode material in supercapacitors, characterized in that, The reduced-modified lignin-based activated carbon is a black powder with a specific surface area of ​​1600.7~2328.59 m². 2 ·g -1 The total pore volume is 0.85~1.21cm. 3 ·g -1 The pore sizes are mainly micropores and mesopores, with micropores having a specific surface area of ​​1450.7~1992.92 m². 2 ·g -1 The micropore volume is 0.7~0.98 cm³. 3 ·g -1 The mesoporous specific surface area is 59.3~99.3 m². 2 ·g -1 The mesopore volume is 0.12~0.25cm³. 3 ·g -1 The bulk density is 0.56~0.85cm³. 3 ·g -1 The particle size distribution is 200nm~2000nm; The method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials is characterized by comprising the following steps: Step 1: Mix an excess of reducing agent with pulping black liquor containing alkali lignin or an alkaline solution containing lignin and react thoroughly. After reacting at 30-60℃ for 8-12 hours, adjust the pH to 1-7 with an inorganic acid to precipitate alkali lignin. Filter, wash, and dry to obtain reduced lignin. Step 2: The reduced lignin described in Step 1 is carbonized under an inert atmosphere. After continuously introducing inert gas and cooling to room temperature, it is washed and dried with water, inorganic acid and organic solvent to obtain primary lignin char. Step 3: Mix the primary lignin char with KOH and / or NaOH activators evenly, and carry out the activation reaction under an inert atmosphere. After continuously introducing inert gas and naturally cooling, wash and dry with water, inorganic acid and organic solvent to obtain reduced modified lignin-based activated carbon.

2. A method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials as described in claim 1, characterized in that, Includes the following steps: Step 1: Mix an excess of reducing agent with pulping black liquor containing alkali lignin or an alkaline solution containing lignin and react thoroughly. After reacting at 30-60℃ for 8-12 hours, adjust the pH to 1-7 with an inorganic acid to precipitate alkali lignin. Filter, wash, and dry to obtain reduced lignin. Step 2: The reduced lignin described in Step 1 is carbonized under an inert atmosphere. After continuously introducing inert gas and cooling to room temperature, it is washed and dried with water, inorganic acid and organic solvent to obtain primary lignin char. Step 3: Mix the primary lignin char with KOH and / or NaOH activators evenly, and carry out the activation reaction under an inert atmosphere. After continuously introducing inert gas and naturally cooling, wash and dry with water, inorganic acid and organic solvent to obtain reduced modified lignin-based activated carbon.

3. The method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials according to claim 2, characterized in that, In step 1, the pulping black liquor containing alkali lignin is wastewater generated in the alkaline pulping process of the papermaking industry; the alkaline solution containing lignin is a sodium hydroxide solution or a potassium hydroxide solution containing lignin.

4. The method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials according to claim 2, characterized in that, In step 1, the reducing agent is one or more of dithionite, sulfurous acid, formamidinium sulfinic acid, sodium borohydride, and potassium borohydride.

5. The method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials according to claim 2, characterized in that, In step 1, the inorganic acid is either hydrochloric acid or sulfuric acid, with a concentration of 0.5~10 mol / L.

6. The method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials according to claim 2, characterized in that, The molecular weight of the reduced lignin is 1500-5000.

7. The method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials according to claim 2, characterized in that, In step 2, the carbonization reaction specifically involves heating the reduced lignin to 500-700℃ at a heating rate of 1-30℃ / min and holding it at that temperature for 1-2 hours.

8. The method for preparing reduction-modified lignin-based activated carbon for supercapacitor electrode materials according to claim 2, characterized in that, In step 3, the activation reaction specifically involves mixing the primary lignin charcoal and the activator at a mass ratio of 1:(3~6) until uniform, and then heating the mixture to 600~800 ℃ at a heating rate of 1~30℃ / min under an inert atmosphere and holding it at that temperature for 1~3h.

9. A conductive ink containing the reduction-modified lignin-based activated carbon for supercapacitor electrode materials as described in claim 1, characterized in that, It is prepared by mixing the reduced modified lignin-based activated carbon, conductive carbon black and binder; The mass ratio of the reduced-modified lignin-based activated carbon, the conductive carbon black, and the binder is (7~8):(1~2):(0.5~1). The adhesive is either polytetrafluoroethylene or polyvinylidene fluoride.

10. The application of a reduction-modified lignin-based activated carbon, comprising the electrode material for supercapacitors as described in claim 1, in the preparation of supercapacitors.

Citation Information

Patent Citations

  • Porous carbon material, and preparation method and application thereof

    CN106185920A

  • Lignin porous carbon NANO sheet, preparation method therefor, and application thereof in super capacitor electrode material

    WO2020103635A1